APPLICATION OF MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE TEACHING OF THE EXACT INTEGRAL - Djumabayev G'ulomjon Xalillayevich; Abdullayeva Shahlo Abduqodir qizi (European Science Publishing, 2024)
In the ever-evolving landscape of education, the integration of modern information and communication technologies (ICTs) has become a pivotal aspect in the teaching and learning of complex mathematical concepts, such as the exact integral. The exact integral, a fundamental notion in the field of calculus, represents a crucial tool for understanding and analyzing the behavior of continuous functions. As the demands of the 21st-century classroom continue to evolve, the strategic application of ICTs has emerged as a powerful means of enhancing the comprehension and mastery of this integral concept. The advent of digital technologies has revolutionized the way educators approach the teaching of the exact integral. One of the most significant advancements in this regard has been the development of interactive, multimedia-based learning platforms. These platforms, which often incorporate dynamic visualizations, simulations, and real-time feedback mechanisms, have proven to be invaluable in helping students develop a deeper understanding of the underlying principles and applications of the exact integral.
Keywords: exact integral, education, ICT, teaching problems, mathematics, theoretical calculus, mathematical operations.